On L-packets and depth for SL2(K) and its inner form - Aubert, A.-M.; Mendes, S.; Plymen, R.; Solleveld, M. (International Journal of Number Theory, 2017)
We consider the group SL2(K), where K is a local non-archimedean field of characteristic two. We prove that the depth of any irreducible representation of SL2(K) is larger than the depth of the corresponding Langlands parameter, with equality if and only if the L-parameter is essentially tame. We also work out a classification of all L-packets for SL2(K) and for its non-split inner form, and we provide explicit formulae for the depths of their L-parameters.